EL DERECHO A LA LIBERTAD DE OPINIÓN PÚBLICA Y SU INCORPORACIÓN COMO FIGURA JURÍDICA EN LA LEY ORGÁNICA DE COMUNICACIÓN, CON LA FINALIDAD DE GARANTIZAR EL DERECHO A LA COMUNICACIÓN DE LOS PROFESIONALES DEL PERIODISMO - Pasaca Corone, Miguel Angel (2016)
Every human progress is admirable: from newspapers, through the electric telegraph, the radio and television to computer networks today . Any progress and modernization of mass media and its degree of achievement, determines human behavior of all citizens. Nowadays, you can no longer speak of individual behavior, mass media helped to form a universal character in every citizen. However, public opinion is not the result of communication between citizens, but a media production that the owners of the media responsible journalism specialists, in order to manipulate the opinion of any citizen. The objective of this research is to determine the conflicts that arise in professional journalism to shape public opinion and the transgressions of the basic rights of communication that are enshrined in the Constitution of the Republic of Ecuador and the Communications Law; and in the course of this work we see that public opinion is not a right but a privilege of certain landowners who control almost all of the media and see that the journalist be the leading figure in the formation of public opinion, not fulfills its social function but according to their political definition defend and propagate the ideas of any social group and discover that we can not speak of independent journalism . 5 And finally the outcome of this investigation will determine that there is no legal regulations requiring tacitly the prevention, control and punishment of manipulation of public opinion, and if continues the absence of a legal figure, can not solve the major conflicts generated in the formation of public opinion. It is therefore necessary to establish a legal standard for communication to protect the most basic rights of communication, with the reform of 17 of the Communications Law, it should incorporate the right to freedom of public opinion, in which will give the professional journalist his real role of social communicator.